Compliance with International Obligations Regarding Refugees, the Civilian Population and Prisoners of War - Stefan, Gheorghe (Journal of Danubian Studies and Research, 2023)
The provisions stipulated by the Hague Convention obligatorily imposed on all belligerent parties the observance and application of the articles provided by the text of the convention. In parallel, an important role will be played by the principles and regulations of the Geneva Convention, adopted in 1929 regarding the status of prisoners of war, which represented the essence of international humanitarian law, from the point of view of international law, and constituted legal obligations that had to be respected only by the signatory states of that act. Compared to the first international act adopted in 1864 in Geneva, under the name of the First Geneva Convention 1 , which limited the conduct of war, the text had been modified in 1906 and later in 1929 2 for a clearer definition of the status of prisoners of war. The merit for the adoption of the 1939 Geneva Convention on the status of prisoners of war goes to the Swiss authorities who, at the initiative of the International Committee of the Red Cross, recommended the adoption of a new convention from 1921 on the treatment of prisoners of war.